Diversification of Waste Ship Mooring Rope Recycling Products as an Effort to Increase the Economic Welfare of the Polewali Mandar "Samboyang" Rope Processing Business Group - Novitasari, Ika; Zulkarnaim, Nuralamsyah; Erwin, Erwin (Abdi Masyarakat, 2024)
The Samboyang Rope Processing Business Group in Babarura Village is the main partner in this activity. Carrying out pelpangang activities in the traditional way using a manual rolling tool. This has implications for the quality of the rope, the time it takes to make anchor ropes. Apart from that, Tinambung sub-district is the only business The largest anchor rope spinner in West Sulawesi. Apart from that, there has been no innovation in diversifying the forms of products produced from processing anchor ship mooring ropes, until now they have only been used as fishing aids or ship ties, and in the economic marketing and digital bookkeeping sectors. needs to be implemented. Then through a community service program carried out according to the needs of the Samboyang Rope Processing Business Group to increase group productivity. In addition, product diversification from ship mooring rope processing provides new opportunities for the group to increase the added value of their products, marketing training and digital bookkeeping, opening up opportunities for the Samboyang rope processing business group to be competitive in a wider market.